Odpowiedź :
Witam.
[tex]a) \: 1 - \frac{3}{14} = \frac{14}{14} - \frac{3}{14} = \frac{11}{14} [/tex]
[tex]1 - \frac{7}{9} = \frac{9}{9} - \frac{7}{9} = \frac{2}{9} [/tex]
[tex]b) \: 3 - \frac{1}{4} = 2 \frac{4}{4} - \frac{1}{4} = 2 \frac{3}{4} [/tex]
[tex]5 - \frac{5}{7} = 4 \frac{7}{7} - \frac{5}{7} = 4 \frac{2}{7} [/tex]
[tex]c) \: 3 \frac{4}{9} - \frac{7}{9} = 2 \frac{13}{9} - \frac{7}{9} = 2 \frac{6}{9 } = 2 \frac{2}{3} [/tex]
[tex]2 \frac{7}{12} - 1 \frac{11}{12} = \frac{31}{12} - \frac{23}{12} = \frac{8}{12} = \frac{2}{3} [/tex]
Pozdrawiam,
Michał
a)
[tex]1 - \frac{3}{14} = \frac{14}{14} - \frac{3}{14} = \frac{11}{14} \\1 - \frac{7}{9} = \frac{9}{9} -\frac{7}{9} = \frac{2}{9}\\b) 3 - \frac{1}{4} = 2\frac{4}{4} - \frac{1}{4}= 2\frac{3}{4} \\5-\frac{5}{7} = 4\frac{7}{7} - \frac{5}{7} = 4\frac{2}{7} \\c) 3\frac{4}{9} - \frac{7}{9} = 2 \frac{13}{9}-\frac{7}{9} = 2\frac{6}{9}= 2\frac{2}{3} \\2 \frac{7}{12} - 1\frac{11}{12} = 1\frac{19}{12} - 1\frac{11}{12} = \frac{8}{12} = \frac{2}{3}[/tex]